417 Identifying Biomarkers of Social Threat Sensitivity Associated with Social Anxiety and Depressive Symptoms in Adolescents - Madison Politte-Corn; Kristin A. Buss (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Increases in anxiety and depression during adolescence may be related to increased biological reactivity to negative social feedback (i.e., social threat sensitivity). Our goal was to identify biomarkers of social threat sensitivity, which may provide unique etiological insight to inform early detection and intervention efforts. METHODS/STUDY POPULATION: Adolescents aged 12-14 (N=84; 55% female; 80% White; 69% annual family income <$70,000) were recruited. Youth viewed a series of happy, neutral, and angry faces while eye-tracking and electroencephalogram (EEG) data were recorded to capture cognitive and neural markers of sensitivity to social threat (i.e., an angry face). Fixation time and time to disengage from angry faces were derived from eye-tracking and event-related potentials were derived from EEG, which index rapid attention capture (P1), attention selection and discrimination (N170), and cognitive control (N2). Adolescents also completed a social stress task and provided salivary cortisol samples to assess endocrine reactivity. Social anxiety and depressive symptoms were self-reported concurrently and one year later. RESULTS/ANTICIPATED RESULTS: Latency to disengage from threatening faces was associated with lower N2 amplitudes (indexing poor cognitive control; r= -.24, p = .03) and higher concurrent social anxiety (r = .28, p = .01). Higher N170 amplitudes, reflecting attentional selection and discrimination in favor of threatening faces, predicted increases in depressive symptoms one year later (b= .88, p = .02). No other neurophysiological measures were associated with each other or with concurrent or prospective symptomatology. DISCUSSION/SIGNIFICANCE: Eye-tracking and EEG measures indexing difficulty disengaging from social threat and poor cognitive control may be biomarkers of social anxiety, which could be utilized as novel intervention targets. High N170 amplitudes to social threat, derived from EEG, may have clinical utility as a susceptibility/risk biomarker for depressive symptoms.